2019
DOI: 10.1016/j.bbe.2019.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Technology-based health promotion: Current state and perspectives in emerging gig economy

Abstract: It has been a decade since smartphone application stores started allowing developers to post their own applications. This paper presents a narrative review on the state-of-the-art and the future of technology used by researchers in the field of mobile health promotion. Researchers build high cost, complex systems with the purpose of promoting health and collecting data. These systems promote health by using a feedback component that "educates" the subject. Other researchers instead use platforms which provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“… 83 , 93 Lastly, many digital public interventions were said not to be guided by known theory and lack sufficient documentation of their processes, making them difficult to replicate. 43 , 94 …”
Section: Resultsmentioning
confidence: 99%
“… 83 , 93 Lastly, many digital public interventions were said not to be guided by known theory and lack sufficient documentation of their processes, making them difficult to replicate. 43 , 94 …”
Section: Resultsmentioning
confidence: 99%
“…As the third step of the development process, the RT team conducted a review of the literature on the application of digital technologies in health promotion and disease management from the perspectives of health promotion practices and computer engineering. Furthermore, the team conducted a state-of-the-art review on modern health data collection and sharing approaches in the context of an emerging gig economy [ 23 ]. The goal was to understand the progress, best practices, and challenges in digital health intervention and provide guidance in designing a theory-driven RT intervention.…”
Section: Overview Of the Development Processmentioning
confidence: 99%
“…Research indicates that exposure is extended by (1) minimizing time-consuming data input and output activities, (2) automating delivery of task reminders and reinforced messages, (3) providing frequent and real-time feedback to intervention participants and staff, (4) offering the ability to tailor the intervention based on baseline information as well as ongoing changes of the behavior targets and the environment, and (5) leveraging the interactive capabilities of mHealth devices to incorporate BCTs [ 10 , 24 ]. By contrast, lack of structured social interactions and social support was a noted weakness of current digital technologies [ 23 , 24 ]. For example, studies have demonstrated that incorporating IP contact enhanced program compliance and participant engagement in mHealth interventions [ 25 , 26 ].…”
Section: Overview Of the Development Processmentioning
confidence: 99%
See 2 more Smart Citations